Colutea nepalensis Sims. - an Important Shrub of Cold Desert Region of India - Singh, R. P.; Jishtu, Vaneet (Indian Forester, 1997)
The study was conducted in the cold desert region of India in the State of Himachal Pradesh and Jammu & Kashmir. Colutea nepale1UJis Sims attains an average height of 1.20 m with 2.50 m2 average crown area. The shrub provides effective soil cover and binds soil over an area of 3.25 m2. The contribution of aboveground biomass was maximum (57.61%) to the total biomass followed by root biomass (42.39%). The taper rate varies from 0.21 to 0.42 in tap-root and 6.17 to O.30inlateral root, which itself is an indication of the strong root system of the species. Stem contributes maximum energy content (4400.0 cal/g dry weight) followed by root (4000.0 cal/g dry weight) and leaves (3270.0 cal/g dry weight) in descending order.